1992
DOI: 10.1128/jb.174.23.7648-7655.1992
|View full text |Cite
|
Sign up to set email alerts
|

In vitro transcription from the Escherichia coli ilvIH promoter

Abstract: Lrp (leucine-responsive regulatory protein) activates the expression of the Escherichia coli ilvIH operon in vivo and mediates the repression of the operon by exogenous leucine. In Lrp (leucine-responsive regulatory protein), a newly recognized global regulatory protein in Escherichia coli, regulates the expression of at least 12 operons (3, 11). Here we address Lrp-mediated regulation of ilvIH, an E. coli operon that encodes an enzyme catalyzing the first step in branchedchain amino acid biosynthesis (2). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Analyses of some of these sites by mutagenesis have provided evidence that they function in vivo and suggest that Lrp binding to promoter regions directly alters operon activity (9,25,30,31). This conclusion was strengthened by results which showed that the positive action of Lrp on ilvIH expression in vivo could be duplicated in a purified in vitro transcription system (35).…”
supporting
confidence: 61%
“…Analyses of some of these sites by mutagenesis have provided evidence that they function in vivo and suggest that Lrp binding to promoter regions directly alters operon activity (9,25,30,31). This conclusion was strengthened by results which showed that the positive action of Lrp on ilvIH expression in vivo could be duplicated in a purified in vitro transcription system (35).…”
supporting
confidence: 61%
“…lrp is in some cases a positive regulator and in others a negative regulator; in some cases leucine is required for action by Lrp, and in other cases leucine is not required. The best-characterized function of Lrp is as the positive transcriptional activator of the ilvIH operon of E. coli (32,39,40). In the absence of leucine in the medium, Lrp stimulates transcription of the ilvIH operon, whereas exogenous leucine results in repression of the ilvIH operon.…”
Section: Resultsmentioning
confidence: 99%
“…(20) Primer extension analysis. Primer extension reactions employing reverse transcriptase were performed as described previously (31), using RNA isolated from strain CV1401 as described previously (2) (25).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro, Lrp binds in a sequence-specific fashion to multiple sites upstream of the ilvIH promoters from E. coli and Salmonella typhimurium (28,30) and bends DNA upon binding (29). Binding of Lrp to these sites is both necessary and sufficient for transcriptional activation of the ilvIH operon (31). Although much has been learned recently about expression of operons regulated by Lrp, less is known about the regulation of the lrp operon itself.…”
mentioning
confidence: 99%